Cause analysis and management control research on financial risk of university. (18th August 2018) - Chen, Wenbin; He, Liying
Abstract: The world–wide higher education has experienced rapid development since the education reform in recent years, and a lot of money has been invested for the university's infrastructure and new campuses expansion. However, the exceed expansion of new campuses make the university's funds allocated from governments and self–held enterprises cannot meet the requirements of university' normal development, and therefore most universities are burdened by a large amount of debts which can bring out a series of financial risks. According to the classification of university financial risk, the risk sources and potential dangers are analyzed in this study, based on which the university financial risk warning index system and the framework of university financial risk integrated control system are obtained, which are both significant for the university financial risk management.